DIFFERENCES ABOUT CALORIE INTAKE MEASUREMENT ACROSS FITNESS DEVICE AND MOBILE APPS - Arnis, Voldemārs; Buliņa, Ramona; Veseta, Una; Upeniece, Irēna; Vīnberga, Indra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Various technologies are increasingly used in sports and fitness classes. Portable fitness devices are the fastest growing fitness trend worldwide in the recent years (Thompson, 2019). More and more people are using fitness bracelets, smart watches, GPS tracking devices and fitness apps on mobile phones. One of the most commonly used functions in both portable fitness devices and stationary technology is the measurement of calories intake. The simplest, most convenient, and cheapest way to measure calorie intake (CI) is smart devices and custom mobile apps (Ramirez, 2018) that store and process data. However, not all of these devices are accurate and objective enough. Aim of the study: to find out and evaluate the calorie intake of a bicycle ergometer and various mobile apps under different physical loads. CI at various physical loads was determined using the MONARK ERGOMEDIC 839E cycling and applications. Comparing the measurement difference between the apps and the ergometer, it was found that the lowest load difference was for all apps, the least difference was for the POLAR app and the highest was for the SAMSUNG app, and the mid to higher load for the SAMSUNG app. App calorie intake figures are closer to those of the ergometer at peak load.